(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article analyzes the role of role-playing games in the development stages of preschool-aged children. During play, children focus not only on the material world of adults but also on adopting social relationships and roles. Play activities develop with age; younger preschoolers tend to prefer individual play, while middle and older preschoolers learn to follow game rules and establish social interactions. The article also discusses symbolic forms of play, drawing, and construction games as key factors that influence children’s thinking and creative abilities.